The Foundation and Role of Zending in the Development of the GKJ Ngulakan Church in Kulon Progo, 1916–1980 - Hesti Kusuma Astuti; Nugraha Nugraha (Warisan: Journal of History and Cultural Heritage, 2024)
This study investigates the foundation and role of Zending in the historical development of the GKJ Ngulakan Church in Kulon Progo from 1916 to 1980. The research aims to examine the establishment of the church and assess the contributions of Zending to its institutional and community growth. Employing the historical method, this study follows a structured approach, including topic selection, heuristics, source verification, interpretation, and historiography. The findings reveal that GKJ Ngulakan was officially established in 1916 by the Dutch Gereformeerd Zending, following the emergence of a Christian congregation in Ngulakan in 1913. Beyond its religious mission, Zending played a transformative role in local education, healthcare, and economic development. Over time, particularly from 1980 onwards, the church witnessed substantial growth, characterized by an increase in baptized members and the institutionalization of synod sessions for pastoral appointments. This study underscores the critical influence of Zending in shaping not only the religious landscape of GKJ Ngulakan but also its broader socio-economic environment, offering new insights into the intersection of missionary activities and local community development.